PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA TOMORO COFFE - Evi Octavia Ramadhani; Dian Sudiantini, Adhwa Luthfia Zhurifa, Al Pasha Egi Viandra, Muhammad Fathir Maulana, Nabilah Syaki (CV. Adiba Aisha Amira, 2024)
This research aims to investigate the interaction between compensation received and the perceived work environment on the level of performance and job satisfaction of employees at Tomoro Coflee. Observational methods have been used to understand how these factors influence each other in the organizational context. Fair compensation and a conducive work environment play an important role in establishing productive and satisfying working conditions. The data is analyzed taking into account various related studies to provide in-depth insight into these dynamics. The case study at Tomoro Coflee illustrates the importance of considering both financial compensation and non-financial aspects of the work environment in human resource management strategies. Holistic management of these factors will help create a more harmonious and supportive work environment, where employees feel supported to make their best contribution. The practical implication of this research is the need for companies to systematically evaluate their compensation policies, strengthen an inclusive and supportive organizational culture, and improve communication between management and employees to ensure fairness and optimal job satisfaction.